Model for risk analysis of financial bankruptcy in agribusiness SMEs of Antioquia - Colombia - Valencia Cárdenas, Marisol; Trochez González, Johanna; Vanegas López, Juan Gabriel; Restrepo Morales, Jorge Anibal (Universidad Pedagógica y Tecnológica de Colombia, 2016)
The risk of bankruptcy in Antioquia’s agribusiness sector has not been extensively explored using statistical modeling, which can provide important elements and trends in order to understand the behavior of this important sector for the regional economy. This paper estimated a linear mixed model, which was used as the response variable the score obtained with Altman’s Z-Score Model, which is a latent index estimated on the basis of observable financial variables and that depending on its value, ranks companies as solvent or insolvent. The Altman’s Index was computed by company and year within the period 2010-2014, using a sample of 214 small and medium-sized companies from different subsector  of the agribusiness sector in Antioquia. The results show that the percentage of firms that enter the area of insolvency increased systematically during the time period from 8.08% in 2010 to 13% in 2014